Análise de falhas em um processo logístico devido à falta de um controle de qualidade - Barreto, Juliana Menna (2004)
To face the conflicting situation of the current global market, it is convenient that the high direction of the companies and their collaborators draw a strategic planning the short, medium and long periods, because the development of a plan ends up being fundamental to the companies that long for a growth perspective in the future, seeking to the conquest of the leadership and the market success. To assure competitive advantage front to the contestants, in the whole company it owes if it submits to changes, mainly in her structure and in her strategy, in order to get to reach a big one differential of market before their contestants. Only with a differentiating factor it is that the organizations will get to remove durable competitive advantage of the market. One of those differentiating factors can be gotten starting from a Logistic System efficient and well structured, that it will only have validity if it be noticed by the customers. It is common that, in the Logistic System, flaws, mistakes that can be resulting of countless internal variables happen and/or outside to the company. However, the customers and the consumers hope to receive the products of the company in accordance with what had been them promised, in other words, products without defects in the aspects that refer to the quality, color, good conditions, amount of the product, among others. When those customers receive a product with averaged characteristics, certainly, all effort spent in the planning, in the elaboration and in the production they were in vain, besides the mission of the logistics not to be in keeping with her reality. A way capable to soften all those damages to the products consists of the application of the Total Quality Management (TQM), as well as in the application of their tools. Through TQM, it is possible to diagnose the company in the factors that are in disagreement with what had been drawn in order to best to evaluate the situation of the no-conformity of the products. With the apply Tools of the Total Quality as Diagram of Ishikawa and Cycle PDCA went possible to detect the processes that possess flaws, allowing the immediate correction of those. Starting from those implantations in the process logistic, the results are watching a medium period, however immediately the apply the companies will be powerful her differential one competitive to the they give to the market products with low index of mishaps, providing larger benefits instead of they arch with extra costs. Through comparisons among two companies of the branch of the furniture, it was possible to detect some fail in the logistic system, for which was suggested and implant the Quality control, aided by the tools of the Quality in order to minimize the current costs of corruptions of the products of the companies in study.